2014
DOI: 10.1016/j.cbpra.2013.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Development of Stepped Care Trauma-Focused Cognitive-Behavioral Therapy for Young Children

Abstract: Young children who are exposed to traumatic events are at risk for developing posttraumatic stress disorder (PTSD). While effective psychosocial treatments for childhood PTSD exist, novel interventions that are more accessible, efficient, and cost-effective are needed to improve access to evidence-based treatment. Stepped care models currently being developed for mental health conditions are based on a service delivery model designed to address barriers to treatment. This treatment development article describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 51 publications
1
32
0
Order By: Relevance
“…Step One consisted of three in‐office therapist‐led sessions (60 min), 11 parent–child meetings at home over 6 weeks using an empirically informed workbook that was based on the Preschool PTSD Treatment manual (Salloum, Scheeringa, Cohen, & Amaya‐Jackson, ), weekly brief phone support, psychoeducation information from NCTSN website, and a website with video demonstrations of relaxation exercises and imaginal and in vivo exposures. For a complete description of Step One see Salloum et al., . If the child responded to Step One, the child proceeded to the maintenance phase for 6 weeks to practice the skills learned.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Step One consisted of three in‐office therapist‐led sessions (60 min), 11 parent–child meetings at home over 6 weeks using an empirically informed workbook that was based on the Preschool PTSD Treatment manual (Salloum, Scheeringa, Cohen, & Amaya‐Jackson, ), weekly brief phone support, psychoeducation information from NCTSN website, and a website with video demonstrations of relaxation exercises and imaginal and in vivo exposures. For a complete description of Step One see Salloum et al., . If the child responded to Step One, the child proceeded to the maintenance phase for 6 weeks to practice the skills learned.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, TF‐CBT was developed into a stepped care model called stepped care TF‐CBT (see Figure S1) in which the first step, Step One, is a parent‐led treatment where the majority of the treatment is provided at home by the parent. The at‐home treatment is supported with three in‐office sessions with the therapist, phone support, and web‐based psychosocial information and video demonstrations (Salloum, Scheeringa, Cohen, & Storch, ). An a priori early responder status criterion after Step One is used to indicate if the child needs more treatment or can end treatment (Salloum, Scheeringa, Cohen, & Storch, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on a search of studies identified in early August 2015 via the www.clinicaltrials.gov website (search terms [“adaptive treatment” or “adaptive intervention” or “adaptive strategy” or “sequential treatment”] crossed with [“children”, “child”, “adolescent” or “youth”], or with the terms [“sequential multiple assignment randomized trial” or “sequential, multiple assignment, randomized trial”]), we wish to note that there is other exciting work on adaptive interventions being done in the areas of adolescent marijuana use (Budney, Stanger, & colleagues, 2014; Kaminer & colleagues, 2012), prevention of oppositional behavior (Dishion et al, 2014), child depression (Eckshtain, 2013), autism (Kasari & colleagues, 2012), college student suicide prevention (Pistorello & colleagues, 2015), child trauma (Salloum, Robst, et al, 2014; Salloum, Scheeringa, Cohen, & Storch, 2014), and child and adolescent obsessive-compulsive disorder (Shavitt & colleagues, 2010). 1 …”
Section: Ongoing and Future Workmentioning
confidence: 99%
“…However, parental perceptions of and engagement with their child's psychological treatment post-trauma have received limited research attention (e.g. Salloum et al 2014). A better understanding of parents' views of providing support to a child with psychological adjustment difficulties following a traumatic event and views about psychological services may enable mental health professionals to provide advice and support that is acceptable and meaningful to parents following child trauma.…”
mentioning
confidence: 99%